An investigation of urinary trace elements as biomarkers for acute kidney injury - Allen, Jennifer (2020)
Acute kidney injury (AKI) is a rapid deterioration in kidney function over hours to days. It is common, affecting 10-20% of all hospital admissions, and can lead to increased mortality, lengthened hospital stay, chronic kidney disease and dialysis dependence. AKI is identified using serum creatinine (SCr) and urine output. These are recognised to be poor and late markers of AKI; with SCr rising 24-48 hours after injury occurs. A need exists for a biomarker to enable earlier detection of AKI in order to allow early interventions and improve patient outcomes. Several existing biomarkers have attempted to fulfil this role, but all have limitations which preclude their generalised use.